2019
DOI: 10.31557/apjcp.2019.20.6.1749
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FLT3 and NPM1 Mutations in Patients with Acute Myeloid Leukaemia

Abstract: Objective:The most frequent acquired molecular abnormalities and important prognostic indicators in patients with Acute Myeloid Leukaemia (AML) are fms-like tyrosine kinase-3 gene (FLT3) and nucleophosmin-1 (NPM1) mutations. Our study aims to develop a cost effective and comprehensive in-house conventional PCR method for detection of FLT3-ITD, FLT3-D835 and NPM1 mutations and to evaluate the frequency of these mutations in patients with cytogenetically normal (CN) AML in our population. Methods: A total of 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Yusoff et al said that the most common genetic abnormality in AML were NPM1 mutations at exon 12 and he found it in approximately 24 to 45% of all AML cases. 11 Gallagher in his study found that more than 50% of normal karyotype-AML cases harbor mutations in the NPM1 gene, and he concluded that it the highest incidence of any mutation in AML. 12 Mencia-Trinchant, et al found that half of his patients with AML have normal cytogenetics whereas 40% to 50% of these patients have NPM1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Yusoff et al said that the most common genetic abnormality in AML were NPM1 mutations at exon 12 and he found it in approximately 24 to 45% of all AML cases. 11 Gallagher in his study found that more than 50% of normal karyotype-AML cases harbor mutations in the NPM1 gene, and he concluded that it the highest incidence of any mutation in AML. 12 Mencia-Trinchant, et al found that half of his patients with AML have normal cytogenetics whereas 40% to 50% of these patients have NPM1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…For FLT3-ITD mutation detection, the primer set used included forward primer 5'-GCA ATT TAG GTA TGA AAG CCA GC -3' (ITD_14F) and reverse primer 5'-CTT TCA GCA TTT TGA CGG CAA CC -3' (ITD_15R) (Integrated DNA Technologies, USA). 14 Polymerase chain reaction (PCR) assay was performed in a total volume of 25 µL of 12.5µL HotStarTaq master mix (Qiagen, Germany), 1 µL (10 µM) of forward and reverse primers respectively, 8.5 µL nuclease-free water, and 2 µL (10 ng/µL) genomic DNA. The PCR conditions included initial denaturation at 95°C for 7 minutes and followed by 35 cycles of denaturation (at 94°C for 1 minute), annealing (at 58°C for 45 seconds), and extension (at 72°C for 1 minute).…”
Section: Flt3-itd Mutation Detectionmentioning
confidence: 99%
“…The primer set utilised for FLT3-D835 mutational analysis was 5'-CCG CCA GGA ACG TGC TTG-3' (D835_F) as the forward primer and 5'-GCA GCC TCA CAT TGC CCC-3' (D835_R) as the reverse primer (Integrated DNA Technologies, USA). 14 The total volume used for the PCR assay was 25 µL, including 12.5 µL Hot Star Taq master mix (Qiagen, Germany), 1 µL (10 mM) of forward and reverse primers respectively, 2.5 µL Q-Solution (Qiagen, Germany), 6 µL nuclease-free water and 2 µL DNA template (10 ng/ml). The PCR conditions were initial denaturation at 95°C for 9 minutes followed by 35 cycles of denaturation (at 94°C for 18 seconds), annealing (at 59°C for 1 minute), and extension (at 72°C for 1 minute).…”
Section: Flt3-d835 Mutation Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed acute myeloid leukemia (AML) as a clinical and biological highly heterogeneous clonal disease that considered originating from hematopoietic stem cells, which characterized by impaired myelopoiesis and blast proliferation (Estey and Döhner, 2006;Saultz and Garzon, 2016). Genome-wide studies using next generation sequencing (NGS), direct sequencing and high-resolution single nucleotide polymorphism (SNP) array have been provided major insight into the panel of the prognostic markers of AML (Liersch et al, 2014;Mat Yusoff et al, 2019). These markers, which encompass genetic mutations, constitute the adoption of risk stratification and therapeutic decision-making in the overall survival of AML patients (De Kouchkovsky and Abdul-Hay, 2016;Kansal, 2016).…”
Section: Introductionmentioning
confidence: 99%